The Potential of TikTok’s Key Features as a Pedagogical Strategy for ESL Classrooms - Tan, Kim Hua; Rajendran, Agila; Muslim, Nazri; Alias, Jamsari; Yusof, Nor Afian (Sustainability, 2022)
The predominance of the use of the English language on social media entails its potential usefulness in regard to ESL learning. Amongst all social media platforms, none can boast the ubiquity of TikTok. This application has been, and continues to be, one of the largest and most influential social media platforms, as well as a massive success across a range of fields with the most active users in the world. In the field of education, it has the potential to enhance educational pedagogies. Although TikTok has various features aligned to language learning, TikTok’s application within the education field is still largely unexplored. This scoping review aims to identify the key features of TikTok that can be used to enhance pedagogical strategies in sustaining the teaching of language skills in ESL classrooms. Although studies have been conducted on this subject, they have often lacked clarity and also lacked the possibility of synthesis in regard to the contribution of this platform to language education. Thus, this scoping review is conducted in order to identify the useful TikTok elements that strengthened pedagogical strategies in ESL classrooms. A total of 60 publications with publication dates spanning from 2018 to 2021 were chosen from searches on the EBSCOhost, Google Scholar, and ERIC databases in order to illustrate the current state. The outcome of using the identified features of TikTok and key pedagogical TikTok strategies for the purposes of ESL learning were the two themes used to synthesize the data. Findings indicated that video-related features and the duet challenge feature in TikTok have potential in promoting engaging and meaningful learning, in the context of a virtual environment. This potential has enabled the use of major pedagogical strategies, such as digital assignment; active learning; collaborative and team-based learning; experiential learning; and incidental and constructive learning. Although using TikTok is beneficial for the purposes of language learning, the findings of this study also revealed several limitations associated with the platform, such as users’ behavior, poor infrastructure, and an absence of online discussion forums. This review contains suggestions for the purposes of assisting teachers in terms of maximizing their use of TikTok, via overcoming the challenges that were highlighted in previous studies.